The Impacts of Parental Communication for adolescence at Tarutung District, North Sumatra Indonesia - Roida Lumbantobing (Conference Series, 2020)
This research aims to determine the positive and significant impacts between parental communication and dealing with juvenile delinquency in Hutatoruan VI Village, Tarutung District, North Tapanuli Regency Indonesia in 2019. This research used a descriptive quantitative method. The research population was all adolescents aged 15-17 years with a total number of 110 people and the sample taken was 45% of the total population or 50 adolescents. The results of data analysis show: 1) Relationship test obtained is rcount> rtable of 0.519> 0.297 and tcount> ttable of 4.206> 2.021; 2) Regression equation obtained is xY40,013,21ˆ; 3) Proportion of influence is %946,22r , which means dealing with juvenile delinquency aged 15-17 years in Hutatoruan Village VI Tarutung Subdistrict, North Tapanuli Regency in 2019 is influenced by parental communication of 26.94%; and 4) Hypothesis Test obtained Fcount> Ftable (17.32> 1.51) which means, it can be concluded that Ho is rejected and Ha is accepted.Parental Communication